2002
DOI: 10.1177/1538192702001001004
|View full text |Cite
|
Sign up to set email alerts
|

Latinos in Higher Education: An Evaluation of a University Faculty Mentoring Program

Abstract: The purpose of this study was to understand the student-faculty mentoring process and how mentoring facilitates Latino students' adjustment to college. Thirty-two Latino students participating in a university Faculty Mentoring Program (FMP) were surveyed. The findings showed that (a) students experienced an increase in college self-efficacy and academic goal definition as a result of participating in the FMP; (b) students with same-ethnic mentors perceived them to be significantly more supportive in furthering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
113
1
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(124 citation statements)
references
References 10 publications
7
113
1
3
Order By: Relevance
“…According to Bandura's theory, verbal persuasion and vicarious learning are two important sources of self-efficacy (Bandura, 1997). Previous studies have found that students who report higher levels of interaction with supportive faculty as mentors and advisors also tend to report higher levels of academic and college self-efficacy (Santos & Reigadas, 2002;Vogt, 2008). Furthermore, in studies with diverse college students, academic self-efficacy mediated the relation of faculty-student interactions to college grades (DeFreitas & Bravo, 2012); college self-efficacy also mediated the relation of environmental supports to self-perceived academic progress (Garriott et al, 2015).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…According to Bandura's theory, verbal persuasion and vicarious learning are two important sources of self-efficacy (Bandura, 1997). Previous studies have found that students who report higher levels of interaction with supportive faculty as mentors and advisors also tend to report higher levels of academic and college self-efficacy (Santos & Reigadas, 2002;Vogt, 2008). Furthermore, in studies with diverse college students, academic self-efficacy mediated the relation of faculty-student interactions to college grades (DeFreitas & Bravo, 2012); college self-efficacy also mediated the relation of environmental supports to self-perceived academic progress (Garriott et al, 2015).…”
Section: Discussionmentioning
confidence: 91%
“…4(1), June 2016 Researchers have argued that, in addition to the typical challenges associated with youth and college life, students from ethnic minority groups experience stressors related to their membership in a socially identified group that has been the target of discrimination and oppression (Contrada et al, 2001;Smedley, Myers, & Harrell, 1993). Ethnic minority status stress emerges as a result of experiencing undesirable situations (e.g.…”
mentioning
confidence: 99%
“…Additionally, engagement with faculty increases Latinx students' sense of belonging (Hurtado & Carter, 1997), social satisfaction (M. E. Levin & J. R. Levin, 1991), and college adjustment and self-efficacy (Santos & Reigadas, 2002). In short, interaction with faculty leads to higher cognitive and non-cognitive outcomes, and increases the retention and graduation of Latinx students.…”
Section: Introductionmentioning
confidence: 99%
“…That being said, some of our conclusions may be applicable to the undergraduate mentor-protégé relationship. Readers interested in undergraduate mentoring and diversity issues are directed to the relevant literature (e.g., Good, Halpin, & Halpin, 2000;Grant-Thompson & Atkinson, 1997;Kim, Goto, Bai, Kim, & Wong, 2001;Santos & Reigadas, 2002).…”
mentioning
confidence: 99%